2011
DOI: 10.1590/s1516-14392011005000051
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Single-Wall carbon nanotubes by heat treatment and supercritical extraction

Abstract: Arc discharge is the most practical method for the synthesis of single wall carbon nanotubes (SWCNT). However, the production of SWCNT by this technique has low selectivity and yield, requiring further purification steps. This work is a study of purification of SWCNT by heat treatment in an inert atmosphere followed by supercritical fluid extraction. The raw arc discharge material was first heat-treated at 1250 °C under argon. The nanotubes were further submitted to an extraction process using supercritical CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The advantages of using SCC over conventional methods for processing of carbon nanomaterials are not only environmental but also chemical and economical. Due to its unique inexpensive, non-toxic, and non-flammable properties and excellent recyclability without energy expenditures, SCC has been used for processing of one dimensional carbon nanostructures [1], synthesis of carbon nanotubes (CNTs) [2,3], patterning of carbon nanomaterials [4], growth of CNTs [5] and carbon nanocages [6], purification of sing-walled CNTs (SWCNTs) [7,8], coating of inorganic nanoparticles [9] and polymers over carbon nanostructured surfaces [10], non-covalent functionalization of CNTs with molecular anchors [11], and preparation of endohedral derivatives of CNTs [12] and CNT/polymer composites [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using SCC over conventional methods for processing of carbon nanomaterials are not only environmental but also chemical and economical. Due to its unique inexpensive, non-toxic, and non-flammable properties and excellent recyclability without energy expenditures, SCC has been used for processing of one dimensional carbon nanostructures [1], synthesis of carbon nanotubes (CNTs) [2,3], patterning of carbon nanomaterials [4], growth of CNTs [5] and carbon nanocages [6], purification of sing-walled CNTs (SWCNTs) [7,8], coating of inorganic nanoparticles [9] and polymers over carbon nanostructured surfaces [10], non-covalent functionalization of CNTs with molecular anchors [11], and preparation of endohedral derivatives of CNTs [12] and CNT/polymer composites [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [11] reported that the fracture toughness of a (ZrB 2 -SiC) composite increases by up to $15% at 2.0 wt.% CNTs. However, it is worth noting that the low starting oxidation temperature of CNTs ($400°C) [13] might degrade the mechanical properties of CNT/(ZrB 2 -SiC) composites at elevated temperatures.…”
mentioning
confidence: 99%
“…Phase equilibrium measurements and modelling of ternary system (carbon dioxide plus ethanol plus palmitic acid) 2010 [138] Chemical characterization and phase behavior of grape seed oil in compressed carbon dioxide and ethanol as co-solvent 2010 [26] High-pressure phase diagram of the drug mitotane in compressed and/or supercritical CO 2 2010 [139] A first-principles simulation model for the thermo-hydraulic performance of fan supplied tube-fin heat exchangers 2010 [140] Material and micronization applications Development of gas sensors coatings by polyaniline using pressurized fluid 2012 [141] Purification of single-wall carbon nanotubes by heat treatment and supercritical extraction 2011 [142] CO 2 geological storage in saline aquifers: Parana basin caprock and reservoir chemical reactivity 2011 [143] Synthesis and characterization of ZnO/PET composite using supercritical carbon dioxide impregnation technology 2011 [144] Economic viability of SFE from peach almond, spearmint and marigold 2011 [145] In vitro release profiles of beta-carotene encapsulated in PHBV by means of supercritical carbon dioxide micronization technique 2011…”
Section: Fundamental and Thermodynamic Studiesmentioning
confidence: 99%